Corticospinal excitability is facilitated by combined action observation and motor imagery of a basketball free throw - Wright, D. J.; Wood, G.; Eaves, D. L.; Bruton, A. M.; Frank, C.; Franklin, Z. C. (Psychology of Sport and Exercise, 2018)
Objectives: This experiment investigated the extent to which independent action observation, independent motor imagery and combined action observation and motor imagery of a sport-related motor skill elicited activity within the motor system. Design and method: Eighteen, right-handed, male participants engaged in four conditions following a repeated measures design. The experimental conditions involved action observation, motor imagery, or combined action observation and motor imagery of a basketball free throw, whilst the control condition involved observation of a static image of a basketball player holding a basketball. In all conditions, single pulse transcranial magnetic stimulation was delivered to the forearm representation of the left motor cortex. The amplitude of the resulting motor evoked potentials were recorded from the flexor carpi ulnaris and extensor carpi ulnaris muscles of the right forearm and used as a marker of corticospinal excitability. Results: Corticospinal excitability was facilitated significantly by combined action observation and motor imagery of the basketball free throw, in comparison to both the action observation and control conditions. In contrast, the independent use of either action observation or motor imagery did not facilitate corticospinal excitability compared to the control condition. Conclusions: The findings have implications for the design and delivery of action observation and motor imagery interventions in sport. As corticospinal excitability was facilitated by the use of combined action observation and motor imagery, researchers should seek to establish the efficacy of implementing combined action observation and motor imagery interventions for improving motor skill performance and learning in applied sporting settings.